Base tranceiver station integration / Norul Amin Mohd Nor - Mohd Nor, Norul Amin (2010)
This project paper presents the process that involved in implementation of Base Transceiver Station (BTS) of Global System for Mobile (GSM) network. The processes include of planning, design, survey, installation and measurement equipment use in the process. After undergoing these processes, the BTS is integrated to the TIMECel network. Data analysis is performed after the integration. The result of the analysis will be used to optimize network utilization.